Nafkah dan Keberlanjutan Penghidupan Komunitas Pesisir di Kabupaten Buru - Idrus Hentihu; M Chairul Basrun Umanailo (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This research aims to find out the form and role of institutional living in ensuring the sustainability of the livelihoods of rural communities. This research was conducted in Wamalana village, Buru Regency, Maluku using a qualitative approach. The results showed that the institutional living in Wamalana village has a relationship with the community in fulfilling the sustainability of livelihoods to survive despite limited circumstances. Various institutional living such as masohi, masaurat, state groups, and parusa has given its role as a social resilience scheme for the community in building the sustainability of livelihoods. The institutional bread is reflected in the tradition of helping the community in building cooperation based on the spirit of brotherly bonds. In the context, development intervention through the empowerment of coastal communities in Buru Regency, various institutional living on various levels can be used as an intervention pathway empowerment program. Meanwhile, for the benefit of further studies on institutional living in the countryside can be focused to see the effect on the level of economic well-being of rural communities measured quantitatively.